2002
DOI: 10.1100/tsw.2002.93
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Phenotypes for the Analysis of Higher Mental Function

Abstract: We outline a strategy to relate normal cognitive processes to candidate genes. First, brain imaging is used to specify a cognitive process "attention" in terms of the neural networks involved. Next, evidence is presented showing that the operation of each network involves a dominant neuromodulator. Then we discuss development of a task designed to measure the efficiency of each network in normal individuals and consider evidence on the independence, reliability, and heritability of the networks. DNA from cheek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 22 publications
(22 reference statements)
2
22
0
Order By: Relevance
“…This independence hypothesis has been supported by a behavioral study in which no correlation in performance was found between the three networks, measured using a behavioral testing procedure (Fan, McCandliss, Sommer, Raz, & Posner, 2002). However, in a larger study using a similar testing procedure, a significant correlation between the orienting and executive control network was found (Fossella, Posner, Fan, Swanson, & Pfaff, 2002). Interactions among other networks were also observed using a slightly modified task (Callejas, Lupianez, & Tudela, 2004).…”
Section: Introductionsupporting
confidence: 57%
“…This independence hypothesis has been supported by a behavioral study in which no correlation in performance was found between the three networks, measured using a behavioral testing procedure (Fan, McCandliss, Sommer, Raz, & Posner, 2002). However, in a larger study using a similar testing procedure, a significant correlation between the orienting and executive control network was found (Fossella, Posner, Fan, Swanson, & Pfaff, 2002). Interactions among other networks were also observed using a slightly modified task (Callejas, Lupianez, & Tudela, 2004).…”
Section: Introductionsupporting
confidence: 57%
“…Moderate to high heritability affirms previous twin study results (see Introduction) and is consistent with molecular genetic studies. For example, the long repeat form of the dopamine D4 receptor gene and variants of the monoamine oxidase A gene associated with lower enzyme expression (which synthesizes dopamine) have been associated with both activation in the anterior cingulate gyrus (Fan, Fossella, Sommer, Wu & Posner, 2003) and behavioral measures of executive attention (Fossella, Posner, Fan, Swanson & Pfaff, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…All the participants were given a variant of the ANT that was developed by Fan and colleagues and has been described in greater detail elsewhere (Fan, Fossella, Sommer, Wu, & Posner, 2003;Fan et al, 2002;Fossella, Posner, Fan, Swanson, & Pfaff, 2002). Briefly, the participants viewed a computer screen from a distance of 65 cm, and their responses were collected via two input keys on a mouse.…”
Section: Stimuli and Designmentioning
confidence: 99%